Possibilities and challenges in public policy for educational equity in Colombia from the Agenda 2030. «Todos Aprender» program (Foro de Educacion, 2023)
Equity is a priority for the development of education policies in Latin America and the Caribbean, whose intention is to contribute to the construction of fairer and more democratic societies in line with the 2030 Agenda. Tracing the path followed by national education policies, in terms of opportunities and challenges, has inspired this paper whose aim is to pinpoint the context and evolution of Colombia’s ‘Todos Aprender’ program (PTA) from an equity perspective. Using a public policy analysis methodology based on documentary review and scientific credibility criteria, the analytical hypothesis is that PTA, without being a public policy, has become a de facto public policy with an impact on improving the quality of learning of preschool and elementary school students. According to the following questions of analysis: What has been the meaning and context of PTA’s evolution? What actors have been involved in PTA during its years of implementation? What has been their role in terms of positions, interests, and tensions? PTA has attempted to provide institutional responses to the lack of quality and equity in education, with changing priorities depending on each political moment. Thus, PTA represents an adaptable reference with pedagogical power from public policy to promote preschool and elementary education in the face of the educational challenges of the 2030 Agenda, promoting actions in teacher training, educational innovation and research, and formative evaluation to promote successful learning for all.